The role of Clinical Geneticists in Hereditary Cancer Management and Research - Hanne Meijers Heijboer (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractHereditary cancer refers to cancers caused by germline mutations in cancer predisposing genes. These mutations confer a significantly increased risk of cancer, are rare, and are in the majority of cases autosomal dominantly inherited. Since the eighties of last century more than 115 cancer predisposing genes have been identified. In many Western countries genetic testing of patients and families with clustering of cancers started early, and was often performed by clinical geneticists (MDs performed the counselling and pedigree analyses) and by molecular biologists (in laboratories within departments of clinical genetics). It turned out to be a long path to fully realize the promise of cancer predisposing genes. The clinical utility of many cancer genetic tests and subsequent risk reducing interventions has not yet been validated and pitfalls in e.g. misinterpretation of genetic variants showed up. However, without doubt genetic testing for mutations will eventually turn out as a strong tool to save lives from early cancer death and will become part of standard cancer care throughout the developed world. Apart from primary surgical prevention, major progress is to be expected in earlier diagnoses, tailored therapies, and possibly chemoprevention. Ideally researchers, clinical geneticists, molecular biologists, surgeons, oncologists, gynaecologists and other professionals will work together to reach this goal.